Propensity Score–Based Analysis of Percutaneous Closure Versus Medical Therapy in Patients With Cryptogenic Stroke and Patent Foramen Ovale: The IPSYS Registry (Italian Project on Stroke in Young Adults). (September 2016) - Pezzini, Alessandro; Grassi, Mario; Lodigiani, Corrado; Patella, Rosalba; Gandolfo, Carlo; Zini, Andrea; DeLodovici, Maria Luisa; Paciaroni, Maurizio; Del Sette, Massimo; Toriello, Antonella; Musolino, Rossella; Calabrò, Rocco Salvatore; et al.
Abstract : Background—: We sought to compare the benefit of percutaneous closure to that of medical therapy alone for the secondary prevention of embolism in patients with patent foramen ovale (PFO) and otherwise unexplained ischemic stroke, in a propensity scored study. Methods and Results—: Between 2000 and 2012, we selected consecutive first-ever ischemic stroke patients aged 18 to 45 years with PFO and no other cause of brain ischemia, as part of the IPSYS registry (Italian Project on Stroke in Young Adults), who underwent either percutaneous PFO closure or medical therapy for comparative analysis. Primary end point was a composite of ischemic stroke, transient ischemic attack, or peripheral embolism. Secondary end point was brain ischemia. Five hundred and twenty-one patients qualified for the analysis. The primary end point occurred in 15 patients treated with percutaneous PFO closure (7.3%) versus 33 patients medically treated (10.5%; hazard ratio, 0.72; 95% confidence interval, 0.39–1.32; P =0.285). The rates of the secondary end point brain ischemia were also similar in the 2 treatment groups (6.3% in the PFO closure group versus 10.2% in the medically treated group; hazard ratio, 0.64; 95% confidence interval, 0.33–1.21; P =0.168). Closure provided a benefit in patients aged 18 to 36 years (hazard ratio, 0.19; 95% confidence interval, 0.04–0.81; P =0.026) and in those with a substantial right-to-left shunt size (hazard ratio, 0.19; 95% confidence interval, 0.05–0.68; P =0.011). Conclusions—: PFO closure seems as effective as medical therapy for secondary prevention of cryptogenic ischemic stroke. Whether device treatment might be more effective in selected cases, such as in patients younger than 37 years and in those with a substantial right-to-left shunt size, deserves further investigation. Abstract : Supplemental Digital Content is available in the text.